The right of material equity in occasional service contracts. Judgment Commentary - Castillo Aguirre, David Mauricio (2021)
The principle of equality and non-discrimination is recognized in the Constitution of the Republic of Ecuador. This constitutional principle, composed of the formal and material dimensions, is also configured as a right that can be demanded by its holders to the competent authorities. This article analyzes the judgment n.º 258-15-SEP-CC (Case n.º 2184-11-EP), through which the Constitutional Court of Ecuador recognized the violation of the right of equality, in its material dimension, of Iliana Leticia Vera Montalván and declared the conditional constitutionality of the regulations that regulate the occasional service contracts in Ecuador in favor of people with disabilities. Through theorétical methods —inductive and synthesisanalysis— the theorétical composition of the principle-right to equality and nondiscrimination is exposed, and then reflects on the arguments used by members of the Constitutional Court to recognize the right to the equality of disabled people who provide occasional services in the public sector. Finally, a critique of the scope of the jurisprudential decision is presented, with emphasis on the collective dimension of the right to equality, in order to debate the effects of the sentence on other vulnerable groups and to outline some conclusions.